2016
DOI: 10.1016/j.pec.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Training health professionals in shared decision making: Update of an international environmental scan

Abstract: This update highlights the need to adapt training programs to interprofessional practice and to evaluate them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
131
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 28 publications
2
131
0
1
Order By: Relevance
“…They might also reflect the significant heterogeneity among SDM training programs [39], not only in their content but in their modes of delivery and evaluation of knowledge acquired. In this era of rapidly growing numbers of SDM training programs [40] and national efforts to offer them on the Web platform, the most effective methods of delivery and evaluation urgently need to be standardized.…”
Section: Discussionmentioning
confidence: 99%
“…They might also reflect the significant heterogeneity among SDM training programs [39], not only in their content but in their modes of delivery and evaluation of knowledge acquired. In this era of rapidly growing numbers of SDM training programs [40] and national efforts to offer them on the Web platform, the most effective methods of delivery and evaluation urgently need to be standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 148, 43 training programmes have been systematically evaluated, but only 37 evaluation reports are available. And few of these studies measured efficacy of the educational program(s) . The programmes vary greatly in what training is delivered, the manner of delivery, and the length of time.…”
Section: Introductionmentioning
confidence: 99%
“…The programmes vary greatly in what training is delivered, the manner of delivery, and the length of time. In addition, the review finds a lack of detail and transparency with regard to the didactic contents . In a recent update of the review, increasing activity in producing SDM trainings is indicated, however, the level of evaluation is still poor and interprofessional approaches to SDM is missing …”
Section: Introductionmentioning
confidence: 99%
“…The authors found a large increase worldwide. However, few programs had been evaluated, most were not tailored to specific clinical areas, and two thirds were multi-professional [2]. The question is: In a subject area where tailoring to the individual person in his context is paramount, do we need to document whether each and every single program works?…”
mentioning
confidence: 99%
“…The Qué bec group does an impressive job by keeping an overview of all training programs available, even those not evaluated [2]. Through EACH and AACH I have met wonderful teachers whose teaching methods have not always been the subject of rigorous evaluation.…”
mentioning
confidence: 99%